MUSTAFA MUHARREM ŞİİRİ - TOPRAK, HATİCE (Fırat Üniveristesi, 2023)
Modern Türk şiirinin önemli şairlerinden biri olan Mustafa Muharrem'in şiirlerinin merkezinde imgenin sonsuz uzamda derinleşen kapıları vardır. Anlamı okuyucunun önüne bir çırpıda sermeyen bu eserlerin, okuyucusunu seçme özelliği vardır ve bu yanıyla şiirler farklı bir özgünlüğe sahiptir. Sanatçı ilk eserlerinden son eserine kadar bu özel imaj sisteminde modern ve geleneksel formları kişisel üslubuna uygun bir tarzda kullanır. Yoğun imge dünyasında manayı sezgilere ve çağrışıma bırakan şairin, dilin realitesinden kurtularak dilsizliğin söylemek istedikleri ile özün başlangıçtaki saflığına eriştirilmesi, şiirinin merkezi perspektifidir. Şiirlerin özel temlerinde tarihi, felsefi, mistik derinlikle modernitenin ve ontolojik boşluğun sancıları yer alır. Metafizik hakikatin kaygısını geleneğin emniyetinde duymaya ve modernitenin insanına duyurmaya çalışır. Bu bakımdan şiiri poetik akıl özelinde yeniden yorumlayan Mustafa Muharrem'in edebî kimliği ve eserleri çalışmamızın kapsamını oluşturmaktadır. Eserlerde öne çıkan temalar ve yapısal unsurlar belirlenerek şiirlerin dil ve üslubu incelenmiştir.

In the center of the poems of Mustafa Muharrem, one of the important poets of modern Turkish poetry, there are the doors of the image deepening in infinite space. These works, which do not reveal the meaning in front of the reader at once, have the feature of choosing the reader, and in this respect, the poems have a different originality. From his first works to his last, the artist uses modern and traditional forms in this special image system in a style that suits his personal style. The central perspective of the poem is that the poet, who leaves the meaning to intuition and association in the world of intense imagery, gets rid of the reality of language and reaches the original purity of the essence with what the mute wants to say. The special themes of the poems include the pains of modernity and ontological emptiness with historical, philosophical and mystical depth. Metaphysics tries to feel the concern of truth in the safety of tradition and to announce it to the people of modernity. In this respect, the literary identity and works of Mustafa Muharrem, who reinterprets poetry in terms of poetic mind, constitute the scope of our study. The language and style of the poems were examined by determining the prominent themes and structural elements in the works.
Poetry of Mustafa Muharrem
Keywords: Türk Dili ve Edebiyatı